2002
DOI: 10.1523/jneurosci.22-05-01752.2002
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Deficiency and Homocysteine Impair DNA Repair in Hippocampal Neurons and Sensitize Them to Amyloid Toxicity in Experimental Models of Alzheimer's Disease

Abstract: Recent epidemiological and clinical data suggest that persons with low folic acid levels and elevated homocysteine levels are at increased risk of Alzheimer's disease (AD), but the underlying mechanism is unknown. We tested the hypothesis that impaired one-carbon metabolism resulting from folic acid deficiency and high homocysteine levels promotes accumulation of DNA damage and sensitizes neurons to amyloid beta-peptide (Abeta) toxicity. Incubation of hippocampal cultures in folic acid-deficient medium or in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
369
3
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 586 publications
(395 citation statements)
references
References 77 publications
18
369
3
5
Order By: Relevance
“…For example, the same concentrations of DNA damaging agents that kill neurons do not kill astrocytes, i.e., the threshold is higher in proliferating cells. Doublestrand breaks are the most dangerous type of DNA damage, and the occurrence of this type of damage is much lower than 8-oxoguanine modification or single-strand breaks; 8-oxoguanine in neurons is associated with hereditary chronic disorders in animal models (Bogdanov et al 2000(Bogdanov et al , 2001Kruman et al 2002). While cell culture models provide clear evidence that cells will either undergo apoptosis if they cannot repair DNA after DNA damage or display dephosphorylated γH2AX following repair, the actual situation in vivo, especially in a chronic disease condition, is likely different than in a cell culture model system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the same concentrations of DNA damaging agents that kill neurons do not kill astrocytes, i.e., the threshold is higher in proliferating cells. Doublestrand breaks are the most dangerous type of DNA damage, and the occurrence of this type of damage is much lower than 8-oxoguanine modification or single-strand breaks; 8-oxoguanine in neurons is associated with hereditary chronic disorders in animal models (Bogdanov et al 2000(Bogdanov et al , 2001Kruman et al 2002). While cell culture models provide clear evidence that cells will either undergo apoptosis if they cannot repair DNA after DNA damage or display dephosphorylated γH2AX following repair, the actual situation in vivo, especially in a chronic disease condition, is likely different than in a cell culture model system.…”
Section: Discussionmentioning
confidence: 99%
“…51,53,54 Recently, experiments with mice have shown that these mechanisms are not only important in cultured embryonic premitotic neurons, but in the adult postmitotic neurons as well. 55 The deleterious effect of MTHFR dysfunction on brain development was observed in individuals with a severe deficiency of this enzyme, resulting in delayed psychomotor development, mental retardation and psychiatric symptoms. 56 The 70% higher risk of schizophrenia for a 5 mmol/l increase in homocysteine observed in our metaanalysis suggests a dose-response relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine, however, has also been shown to be a risk factor in patients with neuropathologically confirmed AD without significant cerebrovascular disease or atherosclerosis [27]. More recent animal studies [40] provide evidence that folic acid deficiency and homocysteine may be directly related to amyloid toxicity by impairing DNA repair in neurons, which results in sensitization to oxidative damage induced by β-amyloid (a protein that is accumulated in excess in AD brains). This suggests a non-vascular mechanism by which folate intake may be related to the development of AD.…”
Section: Discussionmentioning
confidence: 99%